Achieving ISO 9001 Compliance in Agile Software Development Projects at Indonesian Research Institute - Hermawati, Anisa; Raharjo, Teguh; Wayan Trisnawaty, Ni (SAFE-Network, 2024)
In the modern era, e-government provides comprehensive online services. Currently, there is no standardized quality management regulation in development projects. Therefore, it is crucial for Indonesia, especially in one of the Indonesian Institute of Sciences, to consider implementing ISO 9001:2015 in project development. By doing so, it can demonstrate its dedication to efficient project management and quality assurance to improve quality and customer satisfaction, as it can significantly enhance the reputation and credibility of the Institute in the eyes of the public. The main objective of this study was to examine the integration of ISO 9001:2015 standard with Agile methodology. This study evaluated the critical documentation required to fulfill ISO 9001:2015 in Agile-based projects. This research utilizes triangulation methods, which include interviews, observations, and field notes in qualitative research. Aligning Agile practices with the rigorous quality management standards of ISO 9001 is essential when incorporating ISO 9001:2015 principles into Agile project development. This research recommends standard operating procedures for implementing the documentation prerequisites of ISO 9001:2015 in advancing Agile projects in the public sector, particularly at the Indonesian Institute of Sciences, to realize the benefits of integrating Scrum and ISO 9001 in improving the quality of public services.